EDUCATIONAL GAMES PROMOTING FOLK CULTURE THROUGH AI - Tomer, Ritesh; Pallavi; Chandoria, Virendar Kumar; Kaur, Simerpreet; Singh, Pooja; Anjum, Shagufta (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The globalization and the loss of intergenerational transmission are rapidly increasing, which poses a threat to the continuation of folk cultural traditions and necessitates interactive and scalable preservation systems. By combining artificial intelligence with learning game worlds, it is possible to create adaptive storytelling, multimodal cultural simulation, and customizable learning paths that can turn passive consumption of heritage into participatory cultural experience. An experimental architecture was developed based on a multilayer design of cultural knowledge graphs, intelligent AI services, gameplay interaction, and learning analytics that were experimentally tested using controlled learner studies. Quantitative findings indicate better normalized learning gain, better retention, better persistence of engagement, and high expert-validated cultural authenticity than non-adaptive digital learning resources. Semantic coherence and responsible cultural representation was achieved through knowledge-graph grounding and community validation. The results show that AI-based cultural games can be used as both pedagogical resources and living digital preservation ecosystems that can maintain long-term engagement with intangible heritage. Scalable multilingual implementation, immersive XR implementation, and privacy-preserving community-based learning models will continue to be the primary areas of the responsible AI-driven cultural education development.